TOWARD AN INTERPRETATION OF THE QUR’AN: BASED ON RELIGIOUS MODERATION USING THE MAQASHID AL-SHARI’AH APPROACH - Roichatul Jannah El Muttaqin; Muhammad Farih (Institut Agama Islam Negeri Bone, 2026)
Interpretation of the meaning of the Qur'an based on religious moderation is an effort to understand the divine word that has been revealed in a balanced, tolerant, and other manner. This article uses the Maqashid Sharia approach as a basis for interpreting the verses of the Qur'an by paying attention to the main objectives of sharia, namely protecting religion, soul, mind, descendants, and property. Through the literature study method, this study shows that an understanding of the Qur'an that is oriented towards maqashid is able to present Islam as a religion that respects human dignity, encourages peace, and rejects extremism. The results of the analysis show that this approach can strengthen an inclusive, rational, and contextual understanding of religion, thereby strengthening social harmony in a diverse society.